Translating Womanism: A feminist translation analysis of Alice Walker’s The Color Purple and its Finnish translation Häivähdys purppuraa - Hamara, Julia (My University, 2017)
The aim of this thesis is to incorporate the third-wave feminist perspective into a translation analysis of a literary feminist text and its translation from English into Finnish and to examine how the feminist features of the original text are transmitted in the Finnish translation. The thesis comprises a critical third-wave feminist review of feminist translation theory as well as a feminist translation analysis of Alice Walker’s womanist classic Color Purple and its Finnish translation Häivähdys purppuraa by Kersti Juva. The theoretical framework of this thesis is multidisciplinary third-wave feminist translation theory, which combines elements of intersectionality theory, feminist linguistics, discourse analysis, and feminist translation theory. As the research material is a work of black feminism, or womanism, the whole thesis is written through the lens of gender and race, and especially their intersectional nature. The research method is qualitative translation analysis, which is conducted in two parts. The first part is a thematic analysis of the original text, the purpose of which is to detect the womanist content in The Color Purple. The second part comprises a comparative textual analysis of the womanist passages in the original text and the translation. The purpose of the comparative analysis is to determine the linguistic means used to express the feminist ideology and compare their implications in the original and the translation. The main findings from the analysis are that, apart from a few significant differences, the translation retains the thematical and linguistic feminist features of the original. There were instances where the feminist critique of the original lost some of its force, but also instances where the translation was more explicit in its feminist critique than the original. The findings indicate that the third-wave feminist translation analysis is a viable framework for the analysis of literary feminist texts.